Salinity alleviator bacteria in rice (Oryza sativa L.), their colonization efficacy, and synergism with melatonin - Gupta, Amrita; Tiwari, Rajesh Kumar; Shukla, Renu; Singh, Arvind Nath; Sahu, Pramod Kumar (Frontiers in Plant Science, 2023)
In this study, rhizospheric and endophytic bacteria were tested for the alleviation of salinity stress in rice. Endophytic isolates were taken from previous studies based on their salt stress-alleviating traits. The rhizospheric bacteria were isolated from rice and screened based on salt tolerance and plant growth-promoting traits. Molecular identification indicated the presence of class Gammaproteobacteria, Bacillota, and Actinomycetia. Two-two most potential isolates each from rhizospheric and endophytic bacteria were selected for in planta trials. Results showed that microbial inoculation significantly improved germination and seedling vigor under elevated salinity. The confocal scanning laser microscopy showed higher bacterial colonization in inoculated rice roots than in control. Based on this experiment, rhizospheric bacteria Brevibacterium frigoritolerans W19 and endophytic Bacillus safensis BTL5 were selected for pot trial along with a growth-inducing compound melatonin 20 ppm. Inoculation of these two bacteria improved the levels of chlorophyll, proline, phenylalanine ammonia-lyase, catalase, superoxide dismutase, polyphenol oxidase, root-shoot length, and dry weight under elevated salt concentration. The gene expression studies showed modulation of SOD1, CATa, NHX1, and PAL1 genes by the bacterial strains and melatonin application. The inoculation was found to have additive effects with 20 ppm melatonin. This enhancement in dry matter accumulation, compatible solute production, and oxidative stress regulation could help plants in mitigating the ill effects of high salinity. Exploring such a combination of microbes and inducer molecules could be potentially useful in developing stress-alleviating bioformulations.